Assessing psychosocial functioning following childhood acquired brain injury: The Sydney Psychosocial Reintegration Scale for Children. (1st November 2016) - Soo, Cheryl; Tate, Robyn L.; Anderson, Vicki; Beauchamp, Miriam H.; Brookes, Naomi; Catroppa, Cathy; Galvin, Jane; Muscara, Frank
Abstract: Objective : The Sydney Psychosocial Reintegration Scale for Children (SPRS-C) assesses psychosocial functioning in children with acquired brain injury (ABI). This article aims to: (1) describe normative data for the parent-rated SPRS-C and, (2) evaluate the discriminant validity of the SPRS-C. Methods : For Aim 1, participants were parents of typically developing children (TDC) aged 5–14 years ( N  = 200). For Aim 2, participants with ABI were aged 5–14 years ( n  = 26). A matched group of TDC was sampled from the larger normative sample to serve as a control group ( n =  26). Results : For Aim 1, SPRS-C scores across the 10 age-bands were in the higher ranges. Correlation coefficients of SPRS-C total score with child's age and parent occupational skill level were not statistically significant. For Aim 2, SPRS-C scores for the ABI group were significantly lower than the control group. Conclusions : These data provide a guide for clinical interpretation of the SPRS-C for measuring psychosocial functioning in children with ABI.